Security Enhancement Of Information Using Multilayered Cryptographic Algorithm (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The main aim of advanced Cryptographic techniques is to provide data security which helps to avoid data hacking and illegal access of data. Providing data confidentiality and strong peer to peer authentication using the multilayer linear feedback shift register (LFSR) cryptographic technique  to reduce the cost of encryption as well as storage and computation. One Time Pad algorithm developed in multilayer which defines the signal transmission in the medium is used to provide information security. For various levels of bit handling in data communication systems authentication keys are implemented in LFSR cascaded cryptography in both encryption and decryption process. For improved data security cascaded LFSR cryptography is analyzed. While processing an image, two stages of encryption and decryption done using multilayered cryptography which enhances the data security.